Tendensi kesalahan berbahasa jawa pada materi pranatacara siswa kelas X SMA N 1 Karanganyar Kabupaten Kebumen - Oktavia Puspita Dewi; Nur Hanifah Insani (Universitas Lampung, 2023)
Pranatacara as one of the Javanese subjects has numerous benefits for students in social life, including in Kebumen Regency. Unfortunately, students frequently make language errors in maximizing their pranatacara speaking abilities, which are influenced by a region's dialect, with the ngapak dialect in Kebumen district being the subject of this research. The gap in this study lies in the difference of the pranatacara's notion where a pranatacara requires the usage of archaic language but the data generated uses krama inggil language. This study attempts to analyze phonological and morphological errors in class X students' instructional material in pranatacara practice. This research employs descriptive qualitative methods and research validation techniques to extend observations and enhance perseverance. The examination information was as hands-on practice results from 36 class X students of SMA N 1 Karanganyar, Kebumen. Data examination was finished by data decline and the results were then explained using an error investigation table. In this review, it was discovered that error in the pronunciation of the vowel